Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Estimation of pyrophosphate content of sodium pyrophosphate Part 6, (7th June 1974) - British Standards Institution,
No abstract available